Factors Influencing Uremic Pruritus among Patients Undergoing Hemodialysis Therapy - yuza olsi rahmi (Program Studi S1 Ilmu Keperawatan dan Ners IKBIS Surabaya, 2025)
Background: Uremic pruritus is a common dermatological complication experienced by patients with chronic kidney disease undergoing hemodialysis. This condition can decrease comfort, interfere with daily activities, and reduce quality of life. Aim: To determine the factors influencing uremic pruritus in hemodialysis patients.. Method: This quantitative study with a descriptive design was conducted in the Hemodialysis Unit of Dr. M. Djamil General Hospital, Padang. A total of 61 respondents were selected using purposive sampling based on inclusion criteria. Data were collected using a demographic characteristics questionnaire and a Skin Moisture Meter to measure skin moisture, then analyzed univariately to describe frequency distribution, percentage, and the mean value of each variable. Results: The majority of respondents were male (60.7%), had secondary education (60.7%), and were unemployed (60.7%). The average duration of hemodialysis was 32.95 months, the mean Blood Urea Nitrogen (BUN) level was 126.62 mg/dl, and the mean skin moisture value was 16.20, categorized as very dry. Conclusion: emodialysis patients in this study tended to have low skin moisture, which may exacerbate uremic pruritus. Demographic and clinical factors such as gender, education, occupation, duration of hemodialysis, BUN levels, and skin moisture should be considered in the management of uremic pruritus.